2013
DOI: 10.1371/journal.pone.0084126
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Interventions to Improve HPV Vaccination Coverage among 13- to 15-Year-Old Females: Measures Implemented by Local Governments in Japan

Abstract: The purpose of this study was to examine the effect of various community-based interventions in support of HPV vaccination implemented by cities and towns within Tochigi prefecture, Japan with a view to identifying useful indicators which might guide future interventions to improve HPV vaccination coverage in the prefecture. A postal questionnaire survey of all 27 local governments in Tochigi Prefecture was conducted in December 2010. All 27 responded, and 22 provided the exact numbers of the targeted and vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Free-of charge school-based delivery of vaccines in general is an effective way to achieve high vaccination coverage in the adolescent age group [ 18 ]. Since the introduction of HPV vaccination programmes for the primary target group, there have been many reports of the success associated with school-based delivery [ 19 25 ]. This is true also for the Swedish national vaccination programme where the uptake is above 80% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Free-of charge school-based delivery of vaccines in general is an effective way to achieve high vaccination coverage in the adolescent age group [ 18 ]. Since the introduction of HPV vaccination programmes for the primary target group, there have been many reports of the success associated with school-based delivery [ 19 25 ]. This is true also for the Swedish national vaccination programme where the uptake is above 80% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fujiwara et al investigated the effect of various communitybased interventions in Tochigi Prefecture and reported that school-based vaccinations and public subsidies are the most effective methods to improve HPV vaccination coverage, with the combination of a free ticket, direct mail and recalls with public subsidies also being important factors. 12 Although the Ministry of Health, Labor and Welfare began to subsidize the HPV vaccination for girls aged 13-16 years in November 2010 as a transient HPV vaccination program, only approximately 60% of local governments had started the program by the end of fiscal year 2010, which ended in March 2011. 13 Yokohama City started the vaccination program in February 2011, and the target age was extended to 18 years in fiscal year 2012, which is thought to be one of the reasons why students from Patients with cervical cancer are increasing among women in their 20s and 30s.…”
Section: Discussionmentioning
confidence: 99%
“…In general, all these studies described an increase in vaccination coverage in terms of initiation and/or all-doses completion. Nevertheless, a significant effect was found in five out of eight studies (62.5%) evaluating HPV vaccination initiation [47][48][49]52,54] and in three out of eight works (37.5%) reporting all-doses completion [47][48][49]. The ninth study [30] demonstrated the efficacy of a school-based information program together with school-based vaccination for any administered vaccine dose.…”
Section: Multicomponent Interventionsmentioning
confidence: 96%
“…Nevertheless, multicomponent strategies often included information/education interventions (16; Four out of nine (44.4%) multicomponent strategies targeting A/P included an information/education intervention associated with one or more reminder activities [47,[50][51][52]. Two studies (22.2%) included a reminder intervention and a financial incentive for adherence [48,49], and four studies (44.4%) relied also on school-based interventions [30,48,51,53] including the provision of vaccination at school in one case [30]. The study by Zimmerman et al, assessed a strategy called "Four Pillars Transformation Program Practice" that combined communication activities with parents and adolescents with interventions aimed at facilitating access to vaccination [54].…”
Section: Multicomponent Interventionsmentioning
confidence: 99%
See 1 more Smart Citation